Health aspects of Mangrove ecosystem with refference to malaria - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1987)
ABSTRACT In Indonesia, most of the malaria outbreaks reported in the coastal regions were transmitted by Anopheles sundaicus. This species of mosquito breeds in lagoons, man-made brackish water formed due to uncontrolled mangrove deforestation or in not-wellmaintained brackish fish ponds. A new perspective in management of the mangrove ecosystem e.g. creating a mangrove green belt of 4-5 km distance from human settlement, is essential to minimize man-mosquito contact